Education Human Resource Management in the Recruitment of Extraordinary Lecturers - Aneu Nandya Indayanti; Afifah Barkatul Atqiya; Badrudin Badrudin (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
In facing the challenges of the era of Society 5.0, improving the quality of human resources is influenced by the vital role of education. One way to increase the effectiveness of talent in facing the challenges of society 5.0 is to capitalize on the needs of the labor market through recruitment. Through recruitment, an organization or institution can choose an employee who qualified according to existing criteria or characteristics to fill certain required positions. One of the programs available at the Faculty of Tarbiyah and Teacher Training in question is the implementation of the recruitment of educators for Extraordinary Lecturers (Dosen Luar Biasa-LB Lecturer). This is the background for the author to study more deeply about planning management and the recruitment process as well as the direction of the policy for determining LB Lecturers at the Faculty of Tarbiyah and Teacher Training UIN Sunan Gunung Djati Bandung. The research in this article uses a qualitative descriptive method with field study techniques, interviews, and a literature study. The results of this study found that: first, the planning process for the recruitment of LB lecturers at the Faculty of Tarbiyah and Teacher Training starts with analyzing the needs of lecturers, which will be outlined and followed up by the Faculty leadership. Second, the recruitment process for LB lecturers at the Faculty of Tarbiyah and Teacher Training is carried out by disseminating information on lecturer needs, receiving lecturer application data with administrative requirements, carrying out a scheduled selection process with CBT exam stages, interviews and displays of Microteaching. Third, the policy direction for determining the results of the recruitment and selection of LB lecturers at the Faculty of Tarbiyah and Teacher Training is to get superior lecturers who are qualified according to the needs of the Faculty